Partisipasi Masyarakat dan Produsen dalam Pengelolaan Sampah Saset di Kota Depok, Jawa Barat - Rahayuningtyas, Caecilia Meyta; Sodri, Ahyahudin; Astuti, Lina Tri Mugi (Jurnal Aspirasi, 2023)
Plastic is widely used as packaging, thereby increasing plastic production. One form is the use of sachets or multilayer plastic, which are widely used for food packaging and household needs. Packaging using sachets is widely used in Indonesia because the price is more economical. However, the community has not been effective in sorting their household waste, so that a lot of unmanaged plastic waste is wasted and accumulates in landfills. Law Number 18 of 2008 states that every producer is responsible for the waste they produce. However, there are only a few producers who process and recycle their sachet waste, so that scavengers and waste banks also do not accept sachet waste. This has an impact on the environment, where sachet waste is difficult to decompose. The purpose of this research is to analyze community and producer participation in waste management through the implementation of extended producer responsibility (EPR), thereby increasing the plastic circular economy. The location of this research was conducted in Depok City, which disposes of its waste to the Cipayung Landfill, Depok. Cipayung Landfill has exceeded its capacity. This research uses quantitative methods, through observation, questionnaires, and literature studies. Based on this study, it was concluded that the composition of 17 percent sachet waste can be managed with the 3R program (reduce, reuse, and recycle), which is supported by community participation in waste segregation and waste banks in the collection, where waste banks can reduce 20 percent inorganic waste, and are supported by manufacturers with the implementation of EPR.AbstrakDi Indonesia, banyak produsen memilih menggunakan saset plastik karena harganya yang lebih ekonomis dibandingkan bahan kemasan lainnya. Namun, penggunaan saset plastik menimbulkan masalah pengelolaan sampah. Meskipun Undang-Undang Nomor 18 Tahun 2008 tentang Pengelolaan Sampah menyatakan bahwa setiap produsen bertanggung jawab atas sampah yang dihasilkannya, masih sedikit produsen yang mengelola dan mendaur ulang sampah sasetnya. Hal ini menyebabkan pemulung dan bank sampah juga tidak menerima sampah saset. Sebagai akibatnya, sampah plastik yang tidak terkelola menumpuk di tempat pembuangan akhir (TPA) dan memperburuk masalah lingkungan. Penelitian ini bertujuan untuk menganalisis partisipasi masyarakat dan produsen dalam pengelolaan sampah saset melalui penerapan extended producer responsibility (EPR), sehingga meningkatkan ekonomi sirkular plastik. Lokasi penelitian ini dilakukan di Kota Depok, yang membuang sampahnya ke TPA Cipayung, Depok. TPA Cipayung ini sudah melebihi daya tampungnya. Penelitian ini menggunakan metode kuantitatif, dengan teknik observasi, kuesioner, dan studi literatur untuk memperoleh data. Dapat disimpulkan bahwa komposisi sampah saset sebesar 17 persen dapat dikelola dengan program 3R (reduce, reuse, dan recycle) , yang didukung oleh partisipasi masyarakat dalam pemilahan sampah dan bank sampah dalam pengumpulannya. Bank sampah dapat mengurangi 20 persen sampah anorganik dengan cara ini, yang didukung oleh produsen dengan penerapan EPR.